β2 adrenergic receptor desensitization through chronic stimulation of Natural Killer cells - Jürgens, Martin Maria (Technische Universität Dortmund, 2024)
Stress is a ubiquitous phenomenon that impacts the health of populations across all social strata. While acute stress can be beneficial, chronic stress elevates the risk for various diseases. A major part of the body’s stress response operates through the Sympathetic-Adrenal-Medullary (SAM) axis, leading to the release of epinephrine. This stress mediator can impact the immune system and alter the immune defense response. Natural Killer (NK) cells play a critical role in early immune responses, defending against pathogens and malignant cells. During stressful situations, NK cells are recruited to the blood circulation within minutes. The expression of adrenergic receptors, particularly β2 adrenergic receptors (β2AR), renders them sensitive to epinephrine. This study analyzed the response of NK cells to acute and chronic β2AR stimulation. We confirmed that acute β2AR stimulation inhibits NK cell functions in vitro. Epinephrine showed potent inhibitory effects, suppressing the activation of NK cells independent of the activation signal. The β2AR stimulation reduced NK cell adhesion, IFNγ secretion, degranulation, and cytotoxicity. We could show that β2AR stimulation effectively blocked the LFA-1 activity and led to the detachment from its ligand ICAM-1. The effect was rescued through the addition of Propranolol, a beta blocker, or ADRB2 knock out implicating LFA-1 inhibition as critical role for NK cell mobilization. The metabolic analysis revealed that β2AR agonists influenced the metabolic profile upon NK cell activation, leading to a prolonged glycolysis activity displayed by Seahorse ECAR values. In contrast, chronic β2AR stimulation nullified NK cell inhibition. After five days of β2AR treatment, NK cells were no longer responsive to a β2AR agonist. Chronic β2AR stimulation did not alter protein translation but led to receptor phosphorylation through the PKA feedback loop, initiating a G-protein switch and receptor desensitization. The β2AR treatment with long-acting β2 agonist (LABA) Indacaterol and epinephrine displayed different properties. While epinephrine inhibited NK cells only transiently as long as the β2AR agonist was abundant, Indacaterol could not be washed away and continuously stimulated the receptor. For this reason, a single LABA treatment was sufficient to induce NK cell desensitization. However, peripheral NK cells from LABA-treated patients remained responsive to epinephrine. They did not exhibit inhibition but showed an overall correlation in NK cell fitness with asthma severity. Taken together, the transient, inhibitory effect of epinephrine indicate that the hormone plays a crucial role in NK cell recruitment during acute stressful situations while repeated β2AR stimulation leads to desensitization.
Keywords: Natürliche Killer Zellen; Adrenalin; Chronischer Stress; β2 Adrenorezeptor; 540; Stress; Adrenalin